2015
DOI: 10.1038/srep11124
|View full text |Cite|
|
Sign up to set email alerts
|

Manipulating the banana rhizosphere microbiome for biological control of Panama disease

Abstract: Panama disease caused by Fusarium oxysporum f. sp. cubense infection on banana is devastating banana plantations worldwide. Biological control has been proposed to suppress Panama disease, though the stability and survival of bio-control microorganisms in field setting is largely unknown. In order to develop a bio-control strategy for this disease, 16S rRNA gene sequencing was used to assess the microbial community of a disease-suppressive soil. Bacillus was identified as the dominant bacterial group in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
3
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 60 publications
8
98
3
5
Order By: Relevance
“…Therefore, integrated disease management strategies are needed aiming both to reduce the impact of the disease on susceptible varieties and increase the durability of resistant varieties. In this scenario, banana and soil microbiota are hypothesized to play an important role1314 as already shown in other agricultural systems1516. Recently, we showed that AFS lead to shifts within the gammaproteobacterial microbiome of banana plants cultivated in Central America917.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, integrated disease management strategies are needed aiming both to reduce the impact of the disease on susceptible varieties and increase the durability of resistant varieties. In this scenario, banana and soil microbiota are hypothesized to play an important role1314 as already shown in other agricultural systems1516. Recently, we showed that AFS lead to shifts within the gammaproteobacterial microbiome of banana plants cultivated in Central America917.…”
supporting
confidence: 55%
“…The resistance of a microbial community to invasion of pathogens is linked to its level of diversity202122. In addition, it has been reported that plant pathogens can be responsible for drastic shifts and dysbiosis within the plant-associated microbiome23 as well as for long-term dysbiosis within the soil microbiome, resulting in infested soils that are unable to be replanted with susceptible plants for a long time1424. In our study, we found both, dysbiosis in the FOC-infested banana microbiomes and a relationship between disease and microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role played by these three genera for suppressing Ralstonia and Fusarium are still unclear. Xue et al (2015) reported that the relative abundance of Bacillus was negatively correlated with banana disease incidence, while in this study, the relative abundance of Bacillus was positively correlated with pathogen abundance and disease incidence as well as Trichoderma. Previous study observed when plant infected by pathogens, plant roots would secrete more citric acid and fumaric acid to stimulate the chemotaxis response of plant growth promoting rhizobacteria (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 47%
“…Se ha logrado identificar la cepa NJN-6 de Bacillus amyloliquefaciens, que mostró inhibición significativa de Foc in vitro, la cual, al ser combinada con compost, mostró resultados positivos para reducir la marchitez causada por Foc TR4 en China, observándose que la aplicación continua cambió la composición de la rizosfera y la comunidad microbiana al aumentar la diversidad bacteriana Xue et al, 2015).…”
Section: Alternativas De Manejo De La Enfermedadunclassified